2013
DOI: 10.1128/jcm.00351-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Commercially Available Immunoglobulin M Capture Enzyme-Linked Immunosorbent Assay for Diagnosis of Dengue Virus Infection

Abstract: dWe evaluated the FDA-cleared InBios dengue virus (DENV) IgM capture enzyme-linked immunosorbent assay (ELISA) for qualitative detection of anti-DENV IgM antibodies from 79 serum samples obtained from dengue virus-infected patients or suspected dengue cases. The agreement, sensitivity, and specificity of the InBios assay compared to the gold standard in-house DENV IgM capture ELISA were 94, 92, and 94%, respectively. We conclude that the InBios DENV IgM capture ELISA can be effectively used for rapid diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…13 Laboratory evidence of recent DENV infection was defined by detection of DENV RNA by RT-PCR or anti-DENV-IgM antibody by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…13 Laboratory evidence of recent DENV infection was defined by detection of DENV RNA by RT-PCR or anti-DENV-IgM antibody by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Isotype-specific antibody-capture ELISA eliminates the isotype competition for the same antigenic sites and, thus, enhances the sensitivity of the assay. A number of commercially available anti-prM/E ELISA kits for both IgM and IgG detection are commonly used for DENV clinical serodiagnosis, and results from comprehensive evaluations suggest a good correlation of these assays with the gold standard Nt test (12)(13)(14).…”
mentioning
confidence: 99%
“…Compared with the indirect method, it had a higher sensitivity and specificity and was not affected by RF or high concentrations of pathogen IgGs [20,21]. In this study, RF and related pathogen IgGs were tested and demonstrated no correlation between RV IgM and CMV IgM in clinical serum samples.…”
Section: Discussionmentioning
confidence: 89%